2021
DOI: 10.4178/epih.e2021044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the associations between cardiovascular health measured with the CANHEART model and early cognitive impairment in a middle-aged population in Korea

Abstract: Background: Both cardiovascular health (CVH) and inflammation associated with cognition, and inflammation also associated with cardiovascular health. However, related information in the Korean population is limited. The objective of our study was to confirm the influence of inflammation on the association between CVH and cognition in cross-sectional design. Methods: Data were obtained from the Cardiovascular and Metabolic Diseases Etiology Research Center baseline study. Participants who completed fasting seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, global cognitive function could be acquired by calculating Z scores. Except for one study (Jeon et al, 2021), the various risk models were found to be significantly connected with a higher chance of dementia in the future. In this study, CVH levels did not correlate with early cognitive decline in the Korean study population.…”
Section: The Different Cvd Risk Models and Dementia Or Cognitive Declinementioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, global cognitive function could be acquired by calculating Z scores. Except for one study (Jeon et al, 2021), the various risk models were found to be significantly connected with a higher chance of dementia in the future. In this study, CVH levels did not correlate with early cognitive decline in the Korean study population.…”
Section: The Different Cvd Risk Models and Dementia Or Cognitive Declinementioning
confidence: 82%
“…Except for Framingham models, we concluded that nine specific CVD risk models may be associated with dementia and cognitive decline. Five CVD risk models were designed for a single country ( Bao-Shan et al, 2021 ; Jeon et al, 2021 ; Buawangpong et al, 2022 ; Zheng et al, 2022 ; Mun et al, 2023 ). KPS, TCVR, the China-PAR, SCORE2, and the CANHEART health index were developed to measure cardiovascular risk among Korean, Thai, Chinese, European, and Canadian populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation